C60‐ToF SIMS imaging of frozen hydrated HeLa cells. (28th February 2012) - Piwowar, Alan M.; Keskin, Selda; Delgado, Melissa Ortiz; Shen, Kan; Hue, Jonathan J.; Lanekoff, Ingela; Ewing, Andrew G.; Winograd, Nicholas
<x xml:space="preserve">Abstract</x> Sample preparation continues to be a major challenge for SIMS studies of biological materials. Maintaining the native hydrated state of the material is important for preserving both chemical and spatial information. Here, we discuss a method that combines a sample wash and dry protocol followed by plunge‐freezing in liquid ethane for a frozen‐hydrated analysis of mammalian cells (HeLa). This method allows for the removal of the growth medium and maintains the hydrated state of the cells so that they can be prepared frozen‐hydrated without the need for a freeze‐fracture device. The cells, which were grown on silicon, were successfully regrown after the cleaning procedure, confirming that a significant portion of the cells remain undamaged during the wash and dry procedure. Results from preliminary SIMS measurements show that is it possible to detect a large variety of biomolecular signals, including intact lipids from the plasma membrane in the mass range of 700–900 Da from single cells, with little external water interference at the surface. Copyright © 2012 John Wiley & Sons, Ltd.